Do Firm Characteristics Influence Tax Risk? - Fadillah, Muhammad Akmal; Nurul Aisyah (Adpebi Science Series, 2024)
Tax risk, in a way widely defined as gathering from all over the risk that will give rise to the consequences, is not desired from position taxation; one of them is that the amount of taxes is not certain and true tax avoidance. The aim of this study is to examine whether firm characteristics influence firm tax risk. Indicators that become variable characteristics of a company consist of size, profitability, growth in sales, and financial constraints. The population in this research is companies manufacturing listed on the Indonesian Stock Exchange in 2020–2021. The retrieval method used in this research was purposive sampling, and 94 samples were collected. The type of data used is secondary data taken from www.idx.co.id. The result of the study indicated that size, profitability, and growth sales had no effect on tax risk. However, financial constraints are proven to have a significant positive effect on tax risk.